2009
DOI: 10.1088/0031-9155/54/15/001
|View full text |Cite
|
Sign up to set email alerts
|

Accurate helical cone-beam CT reconstruction with redundant data

Abstract: We present a new image reconstruction algorithm for helical cone-beam computed tomography (CT). This algorithm is designed for data collected at or near maximum pitch, and provides a theoretically exact and stable reconstruction while beneficially using all measured data. The main operations involved are a differentiated backprojection and a finite-support Hilbert transform inversion. These operations are applied onto M-lines, and the beneficial use of all measured data is gained from averaging three volumes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, the utilization of those redundant data is desirable in terms of reducing image noise. Therefore, appropriately using all the available data in image reconstruction is essential to noise and dose reduction [8587]. …”
Section: General Dose-reduction Strategiesmentioning
confidence: 99%
“…However, the utilization of those redundant data is desirable in terms of reducing image noise. Therefore, appropriately using all the available data in image reconstruction is essential to noise and dose reduction [8587]. …”
Section: General Dose-reduction Strategiesmentioning
confidence: 99%
“…The notation is exactly the same as that used in Ref. [13] where more extensive details can be found.…”
Section: Dbp-ht On M-linesmentioning
confidence: 99%
“…In Ref. [13], we have shown that this property of the DBP can be employed to efficaciously reduce image noise without significantly changing the spatial resolution. The reconstruction procedure can be described as follows:…”
Section: Dbp-ht On M-linesmentioning
confidence: 99%
See 2 more Smart Citations